Electrochemical Exfoliation of Pillared‐Layer Metal–Organic Framework to Boost the Oxygen Evolution Reaction. (13th March 2018) - Huang, Jin; Li, Yun; Huang, Rui‐Kang; He, Chun‐Ting; Gong, Li; Hu, Qiong; Wang, Lishi; Xu, Yan‐Tong; Tian, Xiao‐Yun; Liu, Si‐Yang; Ye, Zi‐Ming; Wang, Fuxin; et al.
Abstract: Two‐dimensional (2D) materials and ultrathin nanosheets are advantageous for elevating the catalysis performance and elucidating the catalysis mechanism of heterogeneous catalysts, but they are mostly restricted to inorganic or organic materials based on covalent bonds. We report an electrochemical/chemical exfoliation strategy for synthesizing metal–organic 2D materials based on coordination bonds. A catechol functionalized ligand is used as the redox active pillar to construct a pillared‐layer framework. When the 3D pillared‐layer MOF serves as an electrocatalyst for water oxidation (pH 13), the pillar ligands can be oxidized in situ and removed. The remaining ultrathin (2 nm) nanosheets of the metal–organic layers are an efficient catalyst with overpotentials as low as 211 mV at 10 mA cm −2 and a turnover frequency as high as 30 s −1 at an overpotential of 300 mV. Abstract : Extra dünn geschnitten : Ein Metall‐organisches Gerüst (MOF) mit säulenverknüpfter Schichtstruktur, liefert nach elektrochemischer Oxidation und Entfernung der Catechol‐funktionalisierten Säulen nur 2 nm dünne Nanoblätter. Diese Nanoblätter sind effiziente Elektrokatalysatoren der Wasseroxidation bei pH 13 mit niedrigem Überpotential und hoher Umsatzfrequenz (TOF).